Estimating snow-cover trends from space. Issue 11 (November 2018) - Bormann, Kat; Brown, Ross; Derksen, Chris; Painter, Thomas
Extensive evidence reveals that Earth's snow cover is declining, but our ability to monitor trends in mountain regions is limited. New satellite missions with robust snow water equivalent retrievals are needed to fill this gap.